2018
DOI: 10.5624/isd.2018.48.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Fractured styloid process masquerading as neck pain: Cone-beam computed tomography investigation and review of the literature

Abstract: Historically, Eagle syndrome is a term that has been used to describe radiating pain in the orofacial region, foreign body sensation, and/or dysphagia due to a unilateral or bilateral elongated styloid process impinging upon the tonsillar region. Because elongated styloid processes–with or without associated Eagle syndrome–can present with various symptoms and radiographic findings, it can be challenging for healthcare practitioners to formulate an accurate diagnosis. Abnormal styloid anatomy can lead to a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(61 reference statements)
0
2
0
3
Order By: Relevance
“…The fracture of an elongated styloid process is a very rare condition. The fracture is caused by trauma in the vast majority of the cases, although other causes such as dental treatment have been reported [ 9 ]. Arechvo et al [ 10 ] reported that traumatic fracture is often caused by car accidents and can also be caused by dental treatment and tonsillectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The fracture of an elongated styloid process is a very rare condition. The fracture is caused by trauma in the vast majority of the cases, although other causes such as dental treatment have been reported [ 9 ]. Arechvo et al [ 10 ] reported that traumatic fracture is often caused by car accidents and can also be caused by dental treatment and tonsillectomy.…”
Section: Discussionmentioning
confidence: 99%
“…X-ray Computed Tomography Scanner (CT scanner) is an important piece of medical equipment widely used in the healthcare industry. CT Scanning is used for brain [57], neck [58], lungs [59], liver [60], heart [61], and numerous other diagnosis. A typical CT-scan consists of series of planar X-ray scans combined together.…”
Section: Computed Tomography Scanner Based On Open Electronicsmentioning
confidence: 99%
“…Por consiguiente, la TCCB proporciona niveles muy bajos de dosis de radiación para el paciente de acuerdo al principio ALARA es decir tan bajo como sea razonablemente posible (Waites & Drage). La TCCB con reconstrucción 3D constituye en la actualidad el algoritmo de estudio por excelencia para diagnosticar el síndrome de Eagle ya que permite observar con precisión los procesos estiloides y las estructuras anatómicas adyacentes lo que además es de gran valor para una exitosa planificación quirúrgica (Khan et al, 2018).…”
Section: Introductionunclassified